Anomalous origin of left coronary artery from pulmonary artery. Surgical considerations in the adult. - Barrand, K G (1975)
The usually recommended treatment for anomalous origin of a left coronary artery from the pulmonary artery is proximal ligation of the anomalous artery with a saphenous vein bypass graft to restore aortocoronary continuity. In an adult patient with large collateral vessels and with the left coronary artery arising from the back of the pulmonary artery, the technical surgical problems associated with this procedure are formidable. Closure of the orifice of the anomalous left coronary artery from inside the pulmonary artery is suggested as the treatment of choice in such a case.